2022
DOI: 10.3390/polym14153102
|View full text |Cite
|
Sign up to set email alerts
|

Strain Release Behaviour during Crack Growth of a Polymeric Beam under Elastic Loads for Self-Healing

Abstract: The response of polymeric beams made of Acrylonitrile butadiene styrene (ABS) and thermoplastic polyurethane (TPU) in the form of 3D printed beams is investigated to test their elastic and plastic responses under different bending loads. Two types of 3D printed beams were designed to test their elastic and plastic responses under different bending loads. These responses were used to develop an origami capsule-based novel self-healing mechanism that can be triggered by crack propagation due to strain release in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Furthermore, from the experimental results, it is observed that the modulus value of the TPE "cross" origami capsule increases with the strain rate. The experimental results correlate with the material properties that define TPE as a flexible material with more flexible filaments than ABS and TPU [42]. The TPE is less hard than ABS and TPU, due to which the beam surface had a more rubbery texture [43].…”
Section: Discussion Of the Tpe "Cross" Origami Capsule Behavioursupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, from the experimental results, it is observed that the modulus value of the TPE "cross" origami capsule increases with the strain rate. The experimental results correlate with the material properties that define TPE as a flexible material with more flexible filaments than ABS and TPU [42]. The TPE is less hard than ABS and TPU, due to which the beam surface had a more rubbery texture [43].…”
Section: Discussion Of the Tpe "Cross" Origami Capsule Behavioursupporting
confidence: 63%
“…TPE is characterised using the study’s extended research work and scope. The analytical process was similar to that of ABS and TPU [ 41 , 42 ], which involves the capsule deflection at different thicknesses, which is 1–3 mm in our case. From the analysis of 3D curves, as indicated in Figure 10 , it is evident that the plastic regime achieves the maximum value of the applied load at 2 mm and 3 mm.…”
Section: Resultsmentioning
confidence: 78%